Innovative activity as a factor of increasing enterprise’s competitiveness. (ҚазҰУ хабаршысы. Экономика сериясы, 2016)
The past few years in Kazakhstan, interest in innovation has grown considerably – even at the level of governments measures to stimulate innovation began to be taken. In process of economic development of society, more and more increases the value of innovations, and at the present stage innovations become the most important instrument of competitive fight of economic entities at all levels of hierarchy – from separate structural units of the enterprises to the countries and regions in general. Only assimilation of innovative model of development which economically developed countries adhere, could strengthen the competitive position of the organization on internal and external markets. The article offers the author’s vision of innovative activity of the enterprise. Factors of innovative activity and their influence on formation the enterprises’ new management model of innovative activity and competitiveness are considered and systematized.